Visitor Satisfaction at the Multatuli History Museum, Rangkasbitung: A Study on Service Quality Impact - Prihartini, Novy; Purnomo, Pungki (Librarianship in Muslim Societies, 2024)
The Multatuli Museum plays a crucial role in serving public demand for high-quality services, as it supports lifelong learning and offers valuable recreational experiences. This study explores the impact of service quality on visitor satisfaction at the Multatuli Museum in Rangkasbitung. A total of 363 participants were included in the sample, selected through purposive sampling with a minimum age of 17. Respondents represented a broad visitor base, including individuals from Rangkasbitung and other areas who had experienced the full range of the museum's facilities and services. The findings show that the quality of services provided by the museum is rated 'very high,' with a score of 3.44, falling within the 3.25–4.00 range. Similarly, satisfaction with these services was categorized as 'outstanding,' scoring 3.42, also within the 3.25–4.00 interval. The analysis further indicates that the quality of services exerts a substantial influence on visitor satisfaction, contributing to 45.4% of the overall satisfaction score. This significant impact underscores the museum's strong potential to deliver high-caliber visitor experiences and demonstrates a solid foundation for continued excellence. To ensure sustained quality and visitor satisfaction, it is essential that the Multatuli Museum, along with the Lebak Regency Culture and Tourism Office, take ongoing, concrete steps to support and enhance the museum's service offerings. By prioritizing service quality and addressing visitors' evolving needs, the Multatuli Museum reinforces its position as an essential educational and cultural hub, promoting learning and enjoyment.